Muslims, Islamic Law, and the Sociopolitical Reality in the United States (American Journal of Islam and Society, 2000)
Native born African-American Muslims and the Immigrant Muslimcommunity foxms two important groups within the American Muslimcommunity. Whereas the sociopolitical reality is objectively the samefor both groups, their subjective responses are quite different. Both arevulnerable to a “double Consciousness,” i.e., an independently subjectiveconsciousness, as well as seeing oneself through the eyes of theother, thus reducing one’s self-image to an object of other’s contempt.Between the confines of culture, politics, and law on the one hand andthe “Islam as a way of life” on the other, Muslims must express theircultural genius and consciously discover linkages within the diverseMuslim community to avoid the threat of double consciousness.